Caracterización morfológica del espermatozoide del cobayo (Cavia porcellus) en el cantón Latacunga - Loor Cedeño, Alex Israel (2015)
The importance of this research with the theme "Morphological sperm guinea pig (Cavia porcellus) in Latacunga Canton" in which it arises as main objective to determine the sperm morphology guinea pig instruments University laboratories was used and animals that were purchased in different areas of Latacunga. 30 male adult animals technique slicing epidydimis to collect sperm was applied using macroscopic and microscopic tests such as color, pH, individual motility, sperm vitality and sperm concentration was used, the measurement was performed by the infinity program analysis. Guinea pig sperm has an oval head some presented with the distal end flattened and acrosome is clearly displayed, it has a long half piece and its tail is long. Guinea pig sperm have an average of 102.53 microns, the head measures 8.81 microns long and 7.41 microns wide, clearly note the acrosome in the head which has an average of 1.95 microns, the intermediate piece It has an average of 9.31 .mu.m and the tail is about 84.41 microns. It was determined that the color guinea pig semen is creamy white with a mean pH of 7.3%, 86.7% of living sperm, a sperm mobility of 73.5% and 32% of abnormal sperm....